An ocean to ourselves - La Borde, Harold ([Laventille], Trinidad : Longman, 1978)
The dramatic story of the historic voyage across the Atlantic by three Trinidadians.
NLJCols20082021
Keywords: La Borde, Harold, -- 1933-; La Borde, Harold, -- 1933-; Humming Bird (Ketch); Humming Bird (Boat); West Indies author; West Indies setting; Atlantic Ocean; Atlantic Ocean; Voyages by sailing boats: Humming Bird (Boat) Atlantic Ocean, 1958-1960. Personal observations